Mechanical testing of miniature carbon fiber reinforced polymer (CFRP) samples under digital light microscopy (Fracture and Structural Integrity, 2024)
The rapid development of inhomogeneous and anisotropic materials like carbon fiber reinforced polymers (CFRP) with epoxy matrices necessitates a multidisciplinary approach for safe use. This approach should integrate computational modeling and experimental testing across various scales, such as microscopic (
Keywords: carbon fiber reinforced polymers (CFRP); miniature samples; in situ mechanical tests; digital light microscopy; digital image correlation (DIC)